Semeadura direta e convencional para a cultura do amendoim na região do Bolsão Sul-mato-grossense - NOGUEIRA, Lavínia Rodrigues; RIBEIRO, Eduarda Barbosa Esteves; SERON, Cássio de Castro; ARAÚJO, Suleiman Leiser; MARTINS, Murilo Battistuzzi; VENDRUSCOLO, Eduardo Pradi (ANAIS DO ENIC, 2025)
-